Development of “Story of Geometry” Comic with Contextual Approach for Junior High School Students - Devany, G Belinda Chrisvania (FKIP Universitas Muhammadiyah Tangerang, 2024)
The aims of this work is to develop mathematica learning materials in the form of cartoons with a contextual approach that it valids, practice, and effectife in the building material of equal space. This type of research is development research (R&D) using the ADDIE model, i.e. analysis, design, development, implementations and evaluation. The developed media launch was done on February 5, 2024 in the even semester of academis year 2023/2024 at Satya Wacana Salatiga Christian Junior High School with 24 students of class IX C and a mathematics teacher. The results of this study animed to create a comic “geometic story” with an average rating of material experts and an average of of media experts as “very good”, the results of student and teacher responses cartoon media that scored an average of and reported “very good”, the pretest and posttest results were analyzed with the Wilcoxon test to show the effectiveness of the carrier, the label results showed a value of 0.000, which means les than 0.05 so it can be said that it is effective. Based on this, it can be concluded that the develop media is valid, practical, and effective so that it can be used as an educational media to support learning.